FOSTERING LITERACY SKILLS IN KINDERGARTEN THROUGH PROJECT-BASED POP-UP BOOK CRAFTING - Ilyas, Sitti Nurhidayah; Herman, Herman; Parwoto, Parwoto; Asti, A. Sri Wahyuni (Universitas Negeri Makassar, 2024)
This study is an experimental research aimed at determining the influence of project-based pop-up book creafting on literacy skills. The population in this study consists of all kindergarten children in the city of Makassar. The research sample was selected using a probability sampling technique, and the selected kindergartens were Teratai UNM Kindergarten with 15 children and Ceria Kindergarten with 15 children. The study analyzes findings using descriptive analysis techniques and Independent-sample T-test. The results showed that the average post-test score of students who participated in project learning in the creation of pop-up books increased to 83.52, while students who participated in conventional learning reached 66.48. The hypothesis test results showed that the t value was 5.486 with a significance of 0.000, confirming a highly significant difference in literacy skills between the groups that followed project-based learning and conventional learning. Therefore, based on the research findings, improving literacy skills in children requires attention to the learning model used, ensuring that the provided learning activities are suitable and capable of stimulating child development.